Reflexões sobre a racionaldade moderna, sobre a experiência-rememoração e sobre a infância em Walter Benjamin - Guimarães, Conceição Ribeiro (2013)
This thesis aims the study: Reflections on the modern rationality,on the experience-recollection and on the childhood in Walter Benjamin. His scathing critique of the rationalist thinking, at least on the way of his time (20th centure), dealt with children, and, in opposition to this thinking, he presents the child as the subject of childhood. For this research, we mostly investigated the following works of the author: Reflections on the child, toy and education (1932), Magic and technical, political art (1930) and One-Way Street (1931). This thesis was divided in three chapters: the first we situate the author in the context of the Frankfurt School; the second chapter we work on the text: Experience and Poverty and the Storyteller: considerations on the work of Nikolai Leskov, wherein the author criticizes the exaggerated manner of using technique and values the experience and the narration and their importance to human life. Although he assumes its ending and decay, he also brings hope wires showing us rescue possibilities on both the experience and narration. The last part of this investigation, the third chapter,we work on Benjamin’s childhood. The Berliner philosopher reveals through toys, games and children's books who the child really is. According to Benjamin, the child is a being with its own characteristics, able to respond to challenges that are posed by society. In spite of the toy is considered a cultural convention from the adult to child, the kid doesn’t feel like a prisoner of a toy, but uses it in a free way, which means that the kid is the subject on the moment of the recreation. Benjamin, through his study of the child, questions the philosophical thinking that is attached to a system which puts the rational as the only possibility of knowledge. According to the author, the imaginative, creative and sensitive capacity of the child also produces knowledge.